Medullary thyroid cancer: strategy, pitfalls and technical aspects with emphasis on remedial surgery - Makay, Ozer; Bartolo, Vincenzo; Cancellieri, Antonino; Catalfamo, Antonina; Famà, Fausto; Pergolizzi, Francesca Pia; Portinari, Mattia; Donatini, Gianluca; Carcoforo, Paolo; Materazzi, Gabriele; Dionigi, Gianlorenzo (Annals of Thyroid, 2018)
Medullary thyroid cancer (MTC) is a rare neuroendocrine tumor that has specific diagnostic and therapeutic requireents. Currently, imaging tools show great limits to localize all residual MTC foci. Non-invasive imaging is helpful but far from perfect for guiding the re-exploration for loco regional residual MTC. The therapeutic approach is different between sporadic and hereditary MTC. In order to obtain the biochemical and anatomical control the first surgical resection is critical. Calcitonin (Ctn) rate used for MTC recurrence detection as serum marker is definite. Yet it poses a unique challenge notwithstanding its ability in detecting microscopic subclinical disease; it is not clear if patients with evident biological signs of residual MTC should be closely observed when MTC is finally found out through different investigations that localize it, or if a different aggressive approach is necessary including central neck dissection, whether or not associated with ipsilateral or bilateral lateral neck dissection. In all phases of the disease, the co-treatment by physicians with experience in MTC therapy should be sought.